1992
DOI: 10.1002/sia.740180109
|View full text |Cite
|
Sign up to set email alerts
|

Depth profile analysis of aluminium metallization in microelectronics: Optimization of depth resolution

Abstract: Depth protiling of aluminium metallization in microelectronics devices by Auger or S I M S analysis is impeded by the severe sputter-induced roughening which causes a serious loss in depth resolution. This paper discusses strategies to avoid this deteriorating eflect : optimization of the bombardment angle, sample rotation during sputtering and the use of heavy or reactive ions. The best depth resolutions were achieved by sputtering with normal incidence 15 keV 02+ ions. In this case, an interface width of 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…the best depth resolution, was observed using oxygen bombardment at normal incidence, in which case the near-surface regionis are converted to A l z 0 3 . 84 The beneficial effect of oxygen bombardment shows up even at angles between 310" and 40" (cf. Fig.…”
Section: Roughening Due To Heterogeneous Phase Formation and The Use mentioning
confidence: 99%
“…the best depth resolution, was observed using oxygen bombardment at normal incidence, in which case the near-surface regionis are converted to A l z 0 3 . 84 The beneficial effect of oxygen bombardment shows up even at angles between 310" and 40" (cf. Fig.…”
Section: Roughening Due To Heterogeneous Phase Formation and The Use mentioning
confidence: 99%
“…The interfaces (i.e., the transition regions between individual layers) appear relatively broad in these SIMS depth profiles. This broadening is due to ion‐beam‐induced roughening of the polycrystalline metal layers, the sputter rate in metals being dependent on the grain orientation . Careful examination of the data, and data obtained at other ion‐beam energies, suggested that the beginning of a new layer could be reasonably defined as the intensity offset of a characteristic secondary ion (e.g., the TiO − offset will be referred to as the begin of the SrTiO 3 layer).…”
mentioning
confidence: 99%
“…A pyramidal surface topography has developed during sputtering. A more grazing incident sputter ion beam is more effective in terms of depth resolution [4,5]. Hence the depth resolution is improved to ∆z/z = 11.5 %.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance depth resolution the sputter conditions can be optimised. In particular this is done by choosing the appropriate primary ion, reducing the primary ion energy, selecting a more grazing incidence ion impact angle [4,5] or rotating the sample around its surface normal during sputtering to avoid permanent ion channelling on single grains [6,7]. In literature even more complex approaches are reported [8,9].…”
Section: Introductionmentioning
confidence: 99%